2015
DOI: 10.3923/je.2015.95.102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cropping and Irrigation Systems on Population Fluctuation of the African White Rice Stem Borer (Maliarpha separatella Rag) and Damage on Rice

Abstract: Information on the population fluctuation of African white rice stem borer (Maliarpha separatella Ragonot), which is a major rice pest in Kenya, is not known. Availability of such information can assist in the development of an integrated management strategy for the pest. Therefore, a study was conducted at Mwea irrigation scheme in Central Kenya, to investigate the influence of irrigation water provision and cropping systems on population of M. separatella. Farmer fields in different parts of the scheme were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The populations of rice stemborers in Igbogun (mangrove swamp) and Itoikin (rainfed lowland) were observed to be higher than that of the rice field in Agbajege(upland), this is due to the favorable environmental conditions encouraging the proliferation of the rice stemborers in the lowland areas (Alams,1992;Kega et al, 2015). This agrees with Sarwar (2012) and Kega et al (2015) that reported a notable increase in stemborer activities under high humid conditions, while Alam et al (1984) and Ukwungwu (1984) also reported a similar trend of increased activities among rice stem borers in lowland rice fields in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The populations of rice stemborers in Igbogun (mangrove swamp) and Itoikin (rainfed lowland) were observed to be higher than that of the rice field in Agbajege(upland), this is due to the favorable environmental conditions encouraging the proliferation of the rice stemborers in the lowland areas (Alams,1992;Kega et al, 2015). This agrees with Sarwar (2012) and Kega et al (2015) that reported a notable increase in stemborer activities under high humid conditions, while Alam et al (1984) and Ukwungwu (1984) also reported a similar trend of increased activities among rice stem borers in lowland rice fields in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The populations of rice stemborers in Igbogun (mangrove swamp) and Itoikin (rainfed lowland) were observed to be higher than that of the rice field in Agbajege(upland), this is due to the favorable environmental conditions encouraging the proliferation of the rice stemborers in the lowland areas (Alams,1992;Kega et al, 2015). This agrees with Sarwar (2012) and Kega et al (2015) that reported a notable increase in stemborer activities under high humid conditions, while Alam et al (1984) and Ukwungwu (1984) also reported a similar trend of increased activities among rice stem borers in lowland rice fields in Nigeria. Also, Luo et al (2021) reported that Chilo suppressalis survived under high water conditions as they tend to move away quickly when compared to Scirpophaga incertulas Walker, which further explains the ability of striped stemborer colonizing the late planted rice almost immediately after migrating from the early sown rice and over wintering sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation